Implementation of the weight product method as a decision support system in determining young coconut business strategies - Ailsa Rira Sinaga (Jurnal Sains, Teknologi & Komputer, 2026)
Young coconut farming is a micro-enterprise with significant market potential in Indonesia. However, strategic decision-making is often subjective, resulting in suboptimal strategies. This study aims to implement the Weighted Product (WP) method as a decision support system for determining young coconut business strategies. The criteria used include business capital, raw material availability, business location, market potential, and business risk. The strategic alternatives analyzed included expanding branches, improving product quality, and digital marketing. The results showed that digital marketing had the highest preference score, and therefore, it is recommended to be implemented as the primary strategy in developing young coconut businesses.